Analysis of The Influence of Service Quality and Customer Satisfaction on the Intention to Buy 3kg LPG at Pangkalan Rizky Inayah - Nur Cholis; Rifda Fitrianty (INCOME: Innovation of Economics and Management, 2022)
Good service is the key to customer satisfaction so good service must be considered. Good service provides satisfaction and trust to customers who use the company's services or products. The purpose of this study is to find out the impact of good customer satisfaction, the benefits of good customer service satisfaction, high customer satisfaction, high customer satisfaction with purchases, and the benefits of good customer service satisfaction. Happy buying drivers. In accordance with its purpose, this research is used in many ways. The study has different independent service models, when the difference between customer satisfaction and customer satisfaction is different. The purpose of this study is to find out the benefits of service quality and customer satisfaction towards the purpose of purchasing 3kg LPG from Pengklan Rizki Anaya. The results of the study show that the service has been effective and efficient for satisfied customers. Satisfaction is good and important. It has an impact on resilience, and good service. Positive and negative impacts in thinking will return.